2013
DOI: 10.1007/s13337-013-0154-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Jatropha curcas Linn. leaf extracts for its cytotoxicity and potential to inhibit hemagglutinin protein of influenza virus

Abstract: Influenza is a serious respiratory illness which can be debilitating and cause complications that lead to hospitalization and death. Although influenza vaccine can prevent influenza virus infection, the only therapeutic options to treat influenza virus infection are antiviral agents. Given temporal and geographic changes and the shifts in antiviral drug resistance among influenza viruses, it is time to consider natural antiviral agents against influenza virus. Jatropha curcas is known for various medicinal use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 15 publications
0
29
0
Order By: Relevance
“…Finally, the newly synthesized viral ribonucleoproteins (vRNPs) are exported into the cytoplasm, and after packaging, mature virions are released from the cell surface depending on the cleaving of SA receptors by sialidase. Therefore, HA plays a key role in initiating viral infection by binding to SA-containing receptors on the host cells, thus mediating the subsequent viral entry and membrane fusion [9][10][11]. The NA cleaves the specific linkage of the SA receptor, resulting in the release of the newly formed virions from the infected cells [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the newly synthesized viral ribonucleoproteins (vRNPs) are exported into the cytoplasm, and after packaging, mature virions are released from the cell surface depending on the cleaving of SA receptors by sialidase. Therefore, HA plays a key role in initiating viral infection by binding to SA-containing receptors on the host cells, thus mediating the subsequent viral entry and membrane fusion [9][10][11]. The NA cleaves the specific linkage of the SA receptor, resulting in the release of the newly formed virions from the infected cells [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Knnappan et al [21], demonstrated the in vivo antiulcer activity of alcoholic extract of leaves. Furthermore, methanolic and aqueous extracts of leaves of Jatropha curcas L. have been found to inhibit drug-resistant HIV strains and hemagglutinin protein of influenza virus [22,23]. …”
Section: Introductionmentioning
confidence: 99%
“…Postinfection (4 isolates) interaction studies showed IC 50 values ranging from 0.0255-0.4137 mg/mL and 0.00073-0.1278 mg/mL for Aqueous and Methanolic Extracts of the leaves of J. curcas respectively and preinfection (1 isolate) interaction studies showed 100% inhibition by Methanolic and 97.19% inhibition by Aqueous Extract at 25 mg/mL each . Patil et al, (2013) studied the inhibition of hemagglutinin using reducing hemagglutination titre which confirmed that the aqueous and methanolic extract J. curcas leaves have direct effect on the process of virus adsorption leading to its inhibition. The results of this study provide the information which shows the potential of Jatropha extracts in the treatment of influenza A (H1N1) virus infection.…”
Section: Anti-viral Activity:-mentioning
confidence: 82%
“…The CC 50 values were 32.07 mg/mL and 35.5 mg/mL for Aqueous and Methanolic Extracts respectively . According to Patil et al, (2013), aqueous and methanol extracts of the leaves were found to be non toxic to Madin darby canine kidney cells below concentration of 15.57 and 33.62 mg/mL respectively. Root extract appeared to be more active compared to leaf and stem bark on both cell lines.…”
Section: Cytotoxicity:-mentioning
confidence: 99%